2015
DOI: 10.1007/s11031-014-9461-y
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a virtual companion on amusement when watching funny films

Abstract: We investigated the role of a virtual companion and trait cheerfulness on the elicitation of amusement. Ninety participants watched funny films in four conditions: either alone, with a virtual companion laughing or verbally expressing amusement at fixed time points (pre-scripted), or additionally joining the participant's laughter (responsive companion). Amusement was assessed facially and vocally by coding Duchenne Displays and laughter vocalizations. Participants' cheerful mood pre and post the film watching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 41 publications
(57 reference statements)
1
19
0
Order By: Relevance
“…The results of several studies have shown that trait cheerfulness predicts how much individuals profit from humor interventions (e.g., Hofmann et al 2015;Papousek and Schulter 2008). Therefore, it might be considered that trait cheerful individuals respond differently compared to non-trait cheerful individuals when being confronted with a humor intervention.…”
Section: Who Should Be Trained?mentioning
confidence: 99%
“…The results of several studies have shown that trait cheerfulness predicts how much individuals profit from humor interventions (e.g., Hofmann et al 2015;Papousek and Schulter 2008). Therefore, it might be considered that trait cheerful individuals respond differently compared to non-trait cheerful individuals when being confronted with a humor intervention.…”
Section: Who Should Be Trained?mentioning
confidence: 99%
“…This would lead to increased naturalness, as well as impacts on people. Positive mood changes induced by conversational systems equipped with laughter have been demonstrated within ILHAIRE and by others in media consumption setups [131,79,46,35], "affective" installations [77,117,92], and experiments are also covering games with a virtual conversational agent [65]. More specifically, in Niewiadomski et al [79], Hofmann et al [46], When a virtual agent was interactively responding to laughter, the level of contagion associated with spontaneous laughter as well as exhilaration was experienced by the users (Niewiadomski et al [79], Hofmann et al [46]).…”
Section: Application Perspectivesmentioning
confidence: 92%
“…In this case, mutual dependencies and closeness are built between a virtual companion and the user. Last, a past research conducted by Hofmann et al [27] approved that "the presence of a virtual companion (compared to being alone)" led to a higher level of cheerfulness for individuals watching a comedy film. As a result, applying a virtual character properly in an interactive scenario, which functions as both a guide and a companion, may reduce the users' feeling of loneliness and enhance their level of enjoyment.…”
Section: Interaction With a Virtual Charactermentioning
confidence: 99%